DIRI SENDIRI SEBAGAI IDE PENCIPTAAN KARYA LUKIS - Wulancahya, Laila; Fatmawati, Fatmawati (Fakultas Ilmu Budaya, Universitas Brawijaya, 2023)
Humans are living, evolving beings. To evolve emotionally, humans need to understand themselves fully. Meanwhile, the author is a person who has yet to recognize herself. However, during her school days, the author liked to express what she felt by drawing in a sketchbook. These experiences have indirectly shaped the author's personality today. That's why the author creates works that come from the depths of her heart. This journey of self-discovery is accomplished through the creation of artworks.In making this work, the author used Alma M. Hawkins' method of creation. The stages are exploration, improvisation, and shaping. In the exploration stage, the author brainstorms the drawings that she made in school. Images that are considered relevant to the topic of the work will be collected as references for sketching the work. Next, the improvisation process includes processing existing references into several sketches and sketching the final work. Finally, the shaping process will be executed on canvas using acrylic paint. The lightweight nature of acrylic paint makes it easy for the author to stack layers in the painting process. These works are derived from the author's personal experience, hence, the empiricism theory of John Locke is used to examine it. In addition, pop-surrealism is used to pour the contents of the author's head into works that can tell many things.The concept of the author's work is a record of a journey to find herself. This personal subject is expected to be accepted and interpreted differently depending on the personalities of the viewers. The author created 10 paintings, including Artifacts; inside my head; Lonely Planet; somebody that I used to know; eating amaryllis; Undead Ghost; hey kamu, disini!; Memory Box; On That Day, I Saw Flying Fishes; and hari yang cerah untuk mengangkat jemuran.